La loi des coûts comparatifs : proposition vraie, mais non triviale - Eastman, H. (L'Actualité économique, 1976)
AbstractThe case for free trade by the Economic Council of Canada rests on established economic analysis respecting the effect of free trade on industrial organization to induce rationalization, on factor prices to induce international specialization and on innovation to raise productivity and eventually reduce foreign ownership. These effects are not measurable exactly. Hence decision to act requires faith in the reliability of abstract reasoning and comprehension of the logical validity of the theory of comparative advantage.Urgency in adopting free trade policy exists because the spread of common markets is inducing rationalization and specialization elsewhere, because low wage rate countries are developing rapidly in standardized productivity owing to the temporary boom in Canadian exports of oil and gas.Multilateral free trade is unlikely to be achieved in the short-term owing to the disinterest of the principal nations and Canada should reduce its tariffs unilaterally. The political possibility of such a policy is increased by growing public distrust of interventionism.